Pengaruh Model Pembelajaran Aktif, Inovatif, Kreatif, Efektif Dan Menyenangkan (Paikem) Terhadap Kemampuan Kreativitas Fisika Siswa Ditinjau Dari Ranah Kognitif Di Kelas X SMK Negeri 1 Batang Angkola. - Nurhaliza Harahap; Eni Sumanti Nasution; Sri Utami Khoilla Mora Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to determine the effect of the Active, Innovative, Creative, Effective, and Enjoyable Learning (PAIKEM) model on students' physics creativity abilities in terms of cognitive domains in class X SMK Negeri 1 Batang Angkola. This research was conducted at SMK Negeri 1 Batang Angkola with a population of all students in class X SMK Negeri 1 Batang Angkola and as samples were taken 36 students of class X TBSM 1 as the control class and 36 students of class X TBSM 2 as an experimental class using the Simple Random Sampling technique ( random sample). This study uses a quasi-experimental method. The research instrument used a test of students' creative abilities in terms of cognitive domains that were valid and reliable. The data in this study were analyzed using statistical methods. The results showed that there was an influence of the Active, Innovative, Creative, Effective, and Enjoyable Learning Model (PAIKEM) on students' physics creativity abilities in Class X SMK Negeri 1 Batang Angkola. Physics creativity ability of students who use the PAIKEM model is better than students who learn using conventional methods.